2016
DOI: 10.1177/1077559516679514
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foster Parent Training on Parenting Skills and Child Disruptive Behavior

Abstract: Children in foster care are at risk for behavioral and emotional problems that require higher levels of care than other children. To meet these needs and reduce placement disruptions, foster parents require effective parenting skills. Although a number of training models have been evaluated, the findings on the efficacy of foster parent training (FPT) are mixed. We conducted a meta-analysis of the FPT outcome research from 1984 to 2014 to develop a clearer understanding of the impact of such trainings. Fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 45 publications
(61 reference statements)
1
53
0
Order By: Relevance
“…Dorsey et al () report that there are two primary curricula used to train foster parents: Model Approach to Partnerships in Parenting Group Preparation and Selection of Foster and/or Adoptive Families and Foster Parent Resources for Information, Development and Education. Both of these programs are designed to help foster parents determine if fostering is right for them (gatekeeping) rather than skill acquisition (Soloman, Niec, & Schoonover, ). Evaluations of both of these foster parent trainings are rare, and the results of the few evaluations produced mixed results (Festinger & Baker, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorsey et al () report that there are two primary curricula used to train foster parents: Model Approach to Partnerships in Parenting Group Preparation and Selection of Foster and/or Adoptive Families and Foster Parent Resources for Information, Development and Education. Both of these programs are designed to help foster parents determine if fostering is right for them (gatekeeping) rather than skill acquisition (Soloman, Niec, & Schoonover, ). Evaluations of both of these foster parent trainings are rare, and the results of the few evaluations produced mixed results (Festinger & Baker, ).…”
Section: Discussionmentioning
confidence: 99%
“…Providing foster families with strategies to maintain routines may diminish child problem behaviours and increase well-being (Budescu & Taylor, 2013). High-quality foster parent training has been correlated with retention of foster parent licences, longer placement lengths, and foster parent satisfaction (Chipungu & Bent-Goodley, 2004 (Soloman, Niec, & Schoonover, 2017). Evaluations of both of these foster parent trainings are rare, and the results of the few evaluations produced mixed results (Festinger & Baker, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…According to Rodriguez, Blatz, and Elbaum (2014) parents are less involved in their children's education in high school. This shows that parents are less involved with school activities and many parents still lack of sufficient information about parenting the children (Seymour, 2017;Solomon, Niec, & Schoonover, 2017) .The involvement of parents in school is decreasing in activities and programs that have impact on students' achievement (Wang & Sheikh Khalil, 2014). Curry, Jean-Marie, and Adams (2016) also state that parental relationship with the school is still tenuous.…”
Section: Parental Rolesmentioning
confidence: 99%
“…As most team members were new to their positions, the team had an opportunity to establish a new vision for caregiving practices. The results of the integrative review (STRONG, 2017) showed that many models of training and support for caregivers have demonstrated small to medium effect sizes on improving the behaviour of foster children/adolescents, though the evidence is weak in terms of rigour (SOLOMON et al, 2017;URETSKY;HOFFMAN, 2017;VAN ANDEL et al, 2014). Although the content and methods of the models studied were not comprehensively described (BENESH; CUI, 2017; FESTINGER; BAKER, 2013), and their training protocols cannot be freely accessed, the theoretical frames of references of the more effective models could be considered to guide the development of this intervention.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Through discussion, the group selected the following as the theorical frames of reference for the training curriculum: developmental theory; attachment theory, for which there is moderate evidence for the use with younger children (DORSEY et al, 2008;EVERSON-HOCK et al, 2012;HAMBR ICK et al, 2016;KERR;COSSAR, 2014;KINSEY;SCHLÖSSER, 2013); trauma-informed care, for which there is initial evidence of effectiveness (MADIGAN et al, 2017); positive discipline (DURRANT et al, 2017), and resilience (RADLER, 2017). Preference was given to frames of reference compatible with social learning theory, as programs based on social learning theory seem to be stronger both in terms of effect sizes and quality of the trials (HAMBRICK et al, 2016;KINSEY;SCHLÖSSER, 2013;LEVE et al, 2012;SOLOMON et al, 2017;URETSKY;HOFFMAN, 2017). Interventions based on social learning theory help "[…] parents learn to interact with their young children in positive ways" (BENESH; CUI, 2017, p. 553).…”
Section: Objective A: Design Anmentioning
confidence: 99%